Bay lodyans : Haitian popular film culture - Accilien, Cécile, 1973- (State University of New York Press, 2023)
"Considers how popular Haitian films not only provide entertainment but also help audiences in Haiti and the diaspora think through daily challenges"-- Provided by publisher.
Keywords: Motion pictures -- Haiti.; Haitians in motion pictures.; Motion picture producers and directors -- Haiti.; Motion picture industry -- Haiti.; Haitian diaspora.; Cinéma -- Haïti.; Producteurs et réalisateurs de cinéma -- Haïti.; Cinéma -- Industrie -- Haïti.; Haïtiens -- Pays étrangers.; PERFORMING ARTS / Film & Video / History & Criticism.; Haitian diaspora; Motion picture industry; Motion picture producers and directors; Motion pictures; Haiti